2021
DOI: 10.1155/2021/8843390
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Factors Associated with Request for Labor Epidural Analgesia in a Tertiary Obstetric Hospital in Vietnam

Abstract: This study is aimed at examining the sociodemographic factors associated with the utilization of labor epidural analgesia at a large obstetric and gynecology hospital in Vietnam. This was a cross-sectional study of women who underwent vaginal delivery in September 2018 at the Hanoi Obstetrics and Gynecology Hospital. The utilization of epidural analgesia during labor was determined. Univariate and multivariate regression models were applied to evaluate the association between patient demographic and socioecono… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
3
3
0
Order By: Relevance
“…Moreover, women in urban cities had a higher prevalence of EA use than those in rural areas [ 17 ]. The 31 to 40-year age group had a higher prevalence of EA use than the other age groups, which is consistent with the results reported in the literature [ 1 , 18 - 19 ]. In Nigeria, research showed that 72% of women would accept EA and 74% would recommend it to their friends and relatives [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, women in urban cities had a higher prevalence of EA use than those in rural areas [ 17 ]. The 31 to 40-year age group had a higher prevalence of EA use than the other age groups, which is consistent with the results reported in the literature [ 1 , 18 - 19 ]. In Nigeria, research showed that 72% of women would accept EA and 74% would recommend it to their friends and relatives [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…When asked about the presence of complications, 42% of the women thought that it can cause serious complications, compared with 38.7% in Khamis Mushait [5,8,22]. These findings are supported by studies from India [14], Nigeria [19,23], Ethiopia [21], and Vietnam [18], where a considerable number of women have myths regarding the effect of EA on uterine contractions.…”
Section: Discussionmentioning
confidence: 81%
“…In our study, the preference for NLA was less in those who had studied below the secondary level. Similar to our observation, in Vietnam, it has been observed that among mothers, the level of education had an influential role in their decision to opt for NLA [18]. In this study, graduates were four times more likely to use epidural analgesia than those educated up to high school [18].…”
Section: Challenges and Factors For Low Incidencesupporting
confidence: 89%
“…A study using the MCGILL pain questionnaire found that primiparous women experienced a higher level of pain in the first stage of labor than multiparous women [1]. In contrast, a study in Vietnam reported that NLA was preferred more by women aged more than 35 years and those who were multiparous [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is also significant that 75% of those who had utilized epidural analgesia were willing to repeat it in subsequent deliveries. This is in keeping with 8,9,15,18 findings from earlier studies . The willingness to use EA in women who have had it before further reinforces that EA is safe for both 19 mothers and babies as shown in earlier studies .…”
supporting
confidence: 92%